Influence of “X” Fracture, Confining Pressure, and Temperature on Rock Masses’ Failure Process - Yunjuan Chen; Yi Jing; Yanchun Yin; Fuqiang Yin; Chenglong Zhao (Advances in Civil Engineering)
Based on the similarity theory, sandstone was taken as the prototype, and rock-like specimens were made with the strength ratio of 1 : 1. Single “X” fracture and double “X” fractures were prefabricated in rock-like specimen, and crack propagation was studied through the compressive test. An improved discontinuous deformation analysis method (DDARF) was adopted to simulate on the cracking process. Further, other factors should not be ignored such as confining pressure and temperature, which were considered: rock’s crack propagations under loading and unloading with different confining pressures were studied; influences of temperature from 20°C to 300°C on crack propagation were analyzed.